2004
DOI: 10.1051/rnd:2004010
|View full text |Cite
|
Sign up to set email alerts
|

Response of anestrous ewes to the ram effect after follicular wave synchronization with a single dose of estradiol-17?

Abstract: -Anestrous ewes respond to the introduction of rams with either an ovulation within 2-3 days that may be followed by luteal phases of normal or short length, with delayed ovulations (5-6 days later), or with the luteinization of follicles. The aim of this work was to study the relationship between the growth status of the largest follicle present when rams are introduced and the type of ovarian response in non-treated ewes and in ewes treated with estradiol-17β before ram introduction. Thirteen anestrous Corri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…Conception rate on first service was higher than that of the second service on MFR20 and MFR30 groups where the interaction between genders was higher. This finding demystifies the observation that the first estrus due to the male effect could be anovulatory [32] or, if ovulation occurs, corpum luteum is weak, lapses rapidly and leads to occurrence of short estrus cycles [6]. Moreover, it shows that male to female ratios of 1:30 or higher, even under controlled mating, should be reanalyzed and considered for adoption even if total conception rates did not differ between groups.…”
Section: Discussionsupporting
confidence: 55%
“…Conception rate on first service was higher than that of the second service on MFR20 and MFR30 groups where the interaction between genders was higher. This finding demystifies the observation that the first estrus due to the male effect could be anovulatory [32] or, if ovulation occurs, corpum luteum is weak, lapses rapidly and leads to occurrence of short estrus cycles [6]. Moreover, it shows that male to female ratios of 1:30 or higher, even under controlled mating, should be reanalyzed and considered for adoption even if total conception rates did not differ between groups.…”
Section: Discussionsupporting
confidence: 55%
“…To our knowledge, this is the first study to show that a polyunsaturated fatty acid EPA down-regulates diabetes-associated hepatokine SELENOP expression by inactivating SREBP-1c in H4IIEC3 hepatocytes. Several lines of evidence have suggested that -3 PUFAs, such as EPA and docosahexaenoic acid (DHA) protect against high-fat diet-induced insulin resistance (38). Neschen et al (24) demonstrated that EPA protects mice from high-fat diet-induced hepatic insulin resistance by binding directly to peroxisome proliferator-activated receptor ␣ and thus decreasing diacylglycerol levels in the liver of mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, progesterone alone is not effective in synchronising the emergence of a new wave at a predictable time. Conversely, 17β-oestradiol alone induces an initial suppression of serum FSH concentrations, followed by an FSH surge 2-3 days later (Meikle et al 2001;Ungerfeld et al 2004). Recently, a treatment combining medroxiprogesterone and 17β-oestradiol resulted in an FSH surge and emergence of a new wave approximately 3-5 days after oestradiol treatment .…”
Section: Alternatives To Synchronise Follicle Wave Emergencementioning
confidence: 99%